The use of Function/Means Trees for modelling technical, semantic and business functions - Robotham, AJ (Brunel University, 2001)
This paper considers the feasibility of using the function/means tree to create a single tree for a complete motor vehicle. It is argued that function/means trees can be used for modelling technical and semantic functions, but it is an inappropriate method for business functions when one tree of the vehicle is required. Life cycle modelling provides an effective means for determining all the required purpose functions and is considered a more effective method than the function/means tree for this task when the structure and mode of operation of the vehicle is well defined and understood.
Keywords: Function-Means Tree; Technical functions; Semantic functions; Business functions